Monetary policy and long-term interest rates - Gianni Amisano; Oreste Tristani (Quantitative Economics, 2023)
We study the relationship between monetary policy and long-term rates in a structural, general equilibrium model estimated on both macro- and yield-data from the United States. Regime shifts in the conditional variance of productivity shocks, or "uncertainty shocks," are a crucial driver of bond risk premia. We highlight three main results. First, our term premia on 10-year bonds are highly correlated with estimates from the affine literature, even if less markedly volatile. Second, uncertainty shocks also induce an increase in equity premia and exert downward pressure on consumption and inflation. An increase in equity premia will therefore be accompanied by a cut in policy interest rates, even if the policy rule does not directly react to equity prices. This model mechanism is consistent with the empirical evidence on the "Fed put." Third, model-implied long-term inflation expectations are less dogmatically anchored than survey-based measures over the 2000s.
Keywords: C11; C34; E40; E43; E52; 330; Bayesian estimation; Fed put; monetary policy; regime switches; risk premia; term structure of interest rates